Molecular markers and pathway analysis of colorectal carcinoma in the Middle East. Issue 21 (28th July 2015) - Beg, Shaham; Siraj, Abdul K.; Prabhakaran, Sarita; Bu, Rong; Al‐Rasheed, Maha; Sultana, Mehar; Qadri, Zeeshan; Al‐Assiri, Mohammed; Sairafi, Rami; Al‐Dayel, Fouad; Al‐Sanea, Nasser; Uddin, Shahab; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Colorectal cancer (CRC) is one of the most common cancers in the world. A newly proposed integrated pathway comprising traditional, alternate, and serrated pathways by genetic and epigenetic factors was defined recently and hypothesized to play a role in the pathogenesis of CRC; however, to the authors' knowledge, there is a paucity of information regarding these proposed molecular pathways in different ethnic groups. METHODS Molecular characterization of 770 CRC specimens was performed for microsatellite instability, BRAF, and KRAS by polymerase chain reaction and 500 cases for CpG island methylator phenotype (CIMP) high phenotype by MethyLight technology. Tumors were assigned to different molecular pathways and examined for clinicopathological correlation and survival analysis. RESULTS The traditional pathway constituted 33.4% of CRC cases, the alternate pathway comprised 11.6%, and the serrated molecular pathway accounted for only 0.8% of Middle Eastern CRC cases. Approximately 54.2% of CRC cases did not qualify to fit into any pathway and thus were designated as an unassigned group. Molecular pathways were found to be significantly associated with tumor site and grade. A subset of cases with an uncategorized pathway demonstrated a significant survival difference (P = .0079). CONCLUSIONS The serrated pathway was found to account for a very low percentage of the CRC patient cohort in the current study. The unassigned group accounted for the majority of Middle Eastern CRC cases, and therefore methods of CRC pathway analysis might not be applicable to this ethnic group. The current study demonstrates the need to unravel the molecular genetic basis of this disease to further subcategorize these CRC cases. It also identifies a need for further studies on different populations for a better understanding of their exact role and incidence. Cancer 2015;121:3799–3808. © 2015 American Cancer Society.